Evaluating environmental conflict resolution: Practitioners, projects, and the movement. (8th May 2018) - Fisher, Micah; Sablan, Tina
Abstract : Environmental conflict is complex and variable, and over time, a concerted field has developed to study processes for collaboration and resolution. This article examines the evaluations of multistakeholder collaborative processes underpinning the field of Environmental Conflict Resolution (ECR). Specifically, we analyze ECR evaluations from over four decades, across different approaches, geographies, and scales. We also corroborate our findings through interviews and discussions with key scholars and practitioners in the field. We highlight the valuable empirical data from evaluations and point to a three‐pronged approach for reinvigorating evaluations that support practitioners and projects and promote broader ideals of ECR collaboration.